Drug use, misuse and abuse : psychopharmacology in the 21st century - Marczinski, Cecile A. (Hoboken, NJ : Wiley, 2014)
'This book presents a new approach to covering the basic principles and major topics found in a typical psychopharmacology course, while adding the newest exciting and controversial findings in the study of drug use, misuse and abuse. Included in this text are major drugs typically covered in an undergraduate psychopharmacology course, including caffeine, nicotine, cocaine, amphetamines including methamphetamine, alcohol, opiates, marijuana, the hallucinogens, antipsychotics, antidepressants, and antianxiety medications. Moreover, the content emphasizes the latest scientific findings in the field, including advances in imaging the living brain.'--
Includes bibliographical references and index.
Keywords: Drugs; Psychopharmacology; Drug abuse; Drugs -- Physiological effect